A GESTÃO PÚBLICA DA POLÍTICA DE ASSISTÊNCIA EM MUNICÍPIOS DE PEQUENO PORTE: um desafio para enfrentamento da desigualdade social - Édina E. C. Meireles de Souza (Universidade Federal do Maranhão, 2007)
The work deals with the result of a research carried through next to representatives of the executive, legislative and advising municipal of nine small cities of the micron-region of Juiz de Fora - MG, from a specific methodology capable to answer the question about the social definition and management of the politics of Social Assistance and, the social determination, politics and institutional that intervene with its implementation, recognizing them as being of responsibility of the State, directed toward the attendance of necessities determined by society and under fort influences of the local power, what compromises its decentralized politic configuration, democratic and participative in the defense of the rights and in confrontation of the poverty, inequality and exclusion.